Performance of structures in the rural area during the March 8, 2010 Elazig-Kovancilar earthquake - Calayir, Yusuf; Sayin, Erkut; Yon, Burak (Springer, 2012)
An earthquake with a magnitude of M-L = 5.8 has occurred in KovancA +/- lar County of ElazA +/- AY, on March 8, 2010. Many structures have been damaged severely or demolished at this moderate earthquake that occurred on East Anatolia Fault zone. The most important reason for damages and collapses of these structures is the lack of engineering services, in other words, not being constructed properly with respect to the available building codes. In this study, damages of various structures (adobe, masonry, hA +/- mA +/- AY, and reinforced concrete structures, and minarets) have been assessed in Ok double dagger ular and the vicinity villages, where the earthquake damage emerged severely.
Keywords: Elazig-Kovancilar earthquake; Rural structures; Earthquake performance